Role of gut microbiota in liver disease - Albhaisi, Somaya A. M.; Bajaj, Jasmohan S.; Sanyal, Arun J. (American journal of physiology: Gastrointestinal and liver physiology, 2020)
The gut microbiome is the natural intestinal inhabitant that has been recognized recently as a major player in the maintenance of human health and the pathophysiology of many diseases. Those commensals produce metabolites that have various effects on host biological functions. Therefore, alterations in the normal composition or diversity of microbiome have been implicated in various diseases, including liver cirrhosis and nonalcoholic fatty liver disease. Moreover, accumulating evidence suggests that progression of dysbiosis can be associated with worsening of liver disease. Here, we review the possible roles for gut microbiota in the development, progression, and complication of liver disease.